2014
DOI: 10.1371/journal.pone.0105838
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare-Associated Infections and Shanghai Clinicians: A Multicenter Cross-Sectional Study

Abstract: Literature about healthcare-associated infection (HCAI) in China is scarce. A cross-sectional anonymous survey was conducted on 647 clinicians (199 physicians and 448 nurses) from six Shanghai hospitals (grades A–C) to investigate their cognizance, knowledge, attitude, self-reported practice, and risks regarding HCAI with emphasis on precautions. The mean overall score of HCAI knowledge was 40.89±11.4 (mean±SD; range, 13∼72) out of 100 for physicians and 43.48±9.9 (10∼70) for nurses. The respondents generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
0
19
1
5
Order By: Relevance
“…It should also be stressed the need to include in nursing curricula contents targeted to the practice of health and safety at work, not only biosafety, but also the other norms that regulate work in health services, in order to make it safer and focused on the perception of risks by professionals (14,(31)(32)(37)(38)(39)(46)(47)(48)(49)(50)(51) . These studies, which account for 40.0% of the analyzed sample stress that risk perception should be included in continuing education actions, since the way in which health professionals perceive risks is directly related to the protective measures adopted by them.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be stressed the need to include in nursing curricula contents targeted to the practice of health and safety at work, not only biosafety, but also the other norms that regulate work in health services, in order to make it safer and focused on the perception of risks by professionals (14,(31)(32)(37)(38)(39)(46)(47)(48)(49)(50)(51) . These studies, which account for 40.0% of the analyzed sample stress that risk perception should be included in continuing education actions, since the way in which health professionals perceive risks is directly related to the protective measures adopted by them.…”
Section: Discussionmentioning
confidence: 99%
“…The 2nd ICHA higher compliance than physician which nurses achieved higher hand hygiene compliance (93%) than physicians (78%) [9]. Another study showed that nurses were generally better than physicians particularly in hand hygiene, perhaps because nursing job is more patient oriented and compliance demanding meanwhile physician considered play important roles as opinion leaders, decision makers, and role models in clinical environment [1].…”
Section: Hand Hygiene and Its Compliancementioning
confidence: 96%
“…Healthcare-associated Infections (HAIs) become the priority attentions of health authorities worldwide since it became the most frequent adverse event of infections in health care system [1]. World Health Organizations defines HAIs referred to nosocomial or hospital infection as an infection occur in a patient during the process of care in a hospital or other healthcare facility which was not present or incubating at the time of admission [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it guarantees the quality of benefits in a health facility suggests that the hospital is not a risk environment for its different users and populations, as well. The failure or absence of this sector leads to the emergence of nosocomial infections (NIA) more widely today, the infections associated with care and services (IAS) that complicate the state of health of patients (Geberemariyam et al 2018, Zhou et al, 2014. In developed countries, nosocomial infections affect 5% to 15% of patients hospitalized in regular services and up to 50% or more of patients in intensive care units (Nejad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%